Assessment of Optimum Renewable Energy System for the Somalia–Turkish Training and Research Hospital in Mogadishu - Dursun, Sibel; Aykut, Ercan; Dursun, Bahtiyar (MERC, 2021)
Somalia–Turkish Training and Research Hospital in Mogadishu, is only powered by diesel generator currently. In this paper, the energy demand of this hospital is utilized by determining the optimum hybrid renewable energy generating system. By HOMER, a sensitivity analysis has been made with emphasis on three significant variables such as average wind speed, present diesel price, and solar radiation. From the results, it can be said that an optimum system is the standalone wind-diesel-battery storage Hybrid Renewable Energy System (HRES) with the configuration of 1,000 kW wind turbine, 350 kW diesel generator, 250 kW power converters, and 300 batteries. Additionally, the net present cost of the optimum system is calculated to be $5,056,700 and its cost of energy is estimated to be 0.191 $/kWh. The present cost of energy for Somalia is 0.5 $/kWh. This shows that the energy cost for the proposed HRES is cheaper than the conventional one. Lastly, according to the results, it is clear that the wind–diesel–battery storage HRES seems more environment friendly than other HRESs.
Keywords: Somalia; Renewable Power Generating System; Hospital; Environmental Assessment; Hybrid Systems; Renewable Energy